The Influence of Globalization on Political and Social Policies in Indonesia - Sumiati, Sumiati (Civiliza Publishing, Indonesia., 2025)
Globalization has become one of the most influential forces shaping political and social policies in Indonesia, producing both opportunities and challenges for national sovereignty, governance, and cultural identity. This research aims to analyze how globalization influences Indonesia’s political and social policies and to examine the extent to which Indonesia demonstrates agency in responding to global pressures. Employing a qualitative research design, the study was conducted from June to August 2025 in Jakarta, Yogyakarta, and Bandung, with data collected through in-depth interviews, focus group discussions, and document analysis. Findings reveal that globalization has strongly influenced political reforms such as decentralization, democratization, and human rights policies, while also shaping social policies in education, cultural preservation, and social welfare. At the same time, Indonesia demonstrates a dual and hybrid approach, selectively adopting global norms while maintaining national priorities and local identity. Globalization has also generated paradoxical effects, fostering openness and innovation while simultaneously stimulating cultural resistance, social inequality, and identity reassertion. The study concludes that Indonesia exemplifies adaptive globalization, negotiating global pressures with local values and strategic interests. This research contributes theoretically by integrating political and social perspectives in the globalization discourse and practically by providing insights for policymakers to design inclusive, culturally sensitive, and context-responsive policies.